2015
DOI: 10.4269/ajtmh.15-0321
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Exposure is Increased in Pork Butchers from Burkina Faso

Abstract: Abstract. We conducted the first survey of zoonotic risk of Hepatitis E virus (HEV) transmissions in Ouagadougou, Burkina Faso, through the direct contact with pork meat during professional activity. Anti-HEV antibodies were more prevalent in pork butchers, 76% than in the general population, which was 47.8% in 2013 (odds ratio = 3.46, 95% CI = 2.85-4.21, P < 0.001). Among slaughter-aged swine, HEV seroprevalence was of 80%, and HEV RNA was detected in 1% of pork livers. Phylogenetic analysis pointed out HEV g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 16 publications
(16 reference statements)
2
28
2
Order By: Relevance
“…The seroprevalence found in our study is comparable with intermedium (46.9-66.4%) seroprevalences in pigs reported in Germany, 12 Italy, 13 Philippines, 14 Switzerland, 15 and China. 16 In contrast, the seroprevalence found in our studied pigs is lower than those (71.2-90%) reported in pigs in Madagascar, 6 Netherlands, 17 Belgium, 18 France, 19 Burkina Faso, 20 and Norway. 21 However, comparison of HEV seroprevalences among the studies should be interpreted with care because several diagnostic assays were used.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The seroprevalence found in our study is comparable with intermedium (46.9-66.4%) seroprevalences in pigs reported in Germany, 12 Italy, 13 Philippines, 14 Switzerland, 15 and China. 16 In contrast, the seroprevalence found in our studied pigs is lower than those (71.2-90%) reported in pigs in Madagascar, 6 Netherlands, 17 Belgium, 18 France, 19 Burkina Faso, 20 and Norway. 21 However, comparison of HEV seroprevalences among the studies should be interpreted with care because several diagnostic assays were used.…”
Section: Discussioncontrasting
confidence: 80%
“…11 Whereas, intermedium (46.9-66.4%) seroprevalences of HEV infection have been reported in pigs in Germany, 12 Italy, 13 Philippines, 14 Switzerland, 15 and China. 16 In contrast, high (71.2-90%) seroprevalences of HEV infection have been found in pigs in Madagascar, 6 Netherlands, 17 Belgium, 18 France, 19 Burkina Faso, 20 and Norway. 21 The prevalence of HEV infection in pigs in Mexico has been scantily studied.…”
mentioning
confidence: 99%
“…As expected, we observed HEV seroprevalence to increase with the number of working years among the slaughterhouse workers, which could be explained by a longer period of exposure. The results in this study are consistent with similar studies that had shown a high prevalence of HEV infections in people who work in direct contact with pigs, which demonstrate that HEV zoonotic transmissions occur through frequent contacts with pigs (Caruso et al., ; Galiana, Fernández‐Barredo, García, Gómez, & Pérez‐Gracia, ; Traoré et al., ). The results indicate that close contact with rabbits poses a risk of HEV infection.…”
Section: Discussionsupporting
confidence: 92%
“…Higher seroprevalence of anti-HEV antibodies was found in swine workers and veterinarians in the United States [180,181]; in swine veterinarians in France [137] and the Netherlands [145]; in swine farmers in Sweden [182], France [137] and Moldovia [183]; and in pork butchers in Burkina Faso [184]. In addition, higher HEV seroprevalence was detected among French hunters [100] and among forestry workers in France [137,185] and Germany [186].…”
Section: Transmission Pathways Of Zoonotic Hevmentioning
confidence: 99%